The Search for Biomarkers and Treatments in Chagas Disease: Insights From TGF-Beta Studies and Immunogenetics - Ferreira, Roberto Rodrigues; Waghabi, Mariana Caldas; Bailly, Sabine; Feige, Jean-Jacques; Hasslocher-Moreno, Alejandro M.; Saraiva, Roberto M.; Araujo-Jorge, Tania C. (Frontiers in Cellular and Infection Microbiology, 2022)
The anti-inflammatory cytokine transforming growth factor beta (TGF-beta) plays an important role in Chagas disease (CD), a potentially life-threatening illness caused by Trypanosoma cruzi. Our clinical studies in CD patients combined with in vitro and in vivo experiments engendered the following concepts: (1) TGF-beta modulates heart cells invasion by T. cruzi; (2) TGF-beta fosters intracellular parasite cycle; (3) TGF-beta modulates host immune response and inflammation; (4) TGF-beta increases heart fibrosis and stimulates remodeling; (5) TGF-beta reduces heart conduction via gap junction modulation; (6) TGF-beta signaling inhibitors reverts these effects opening a promising therapeutic approach; (7) CD patients with higher TGF-beta1 serum levels show a worse clinical outcome, implicating (8) a predictive value T. crof serum TGF-beta as a surrogate biomarker of clinical value; (9) In pre-clinical studies in chronic T. cruzi infected mice, inhibition of TGF-beta pathway improved several cardiac electric parameters, reversed the loss of connexin-43 enriched intercellular plaques, reduced fibrosis of the cardiac tissue, restored GATA-6 and Tbox-5 transcription, supporting cardiac recovery; (10) TGF-beta polymorphisms indicate that CD immunogenetics is at the base of this phenomenon. We searched in a Brazilian population five single-nucleotide polymorphisms (-800 G>A, -509 C>T, +10 T>C, +25 G>C, and +263 C>T). CD patients showed more frequently the TGF-beta1 gene genotypes CT and TT at position -509, compared to noninfected persons, and similar results were observed with genotypes TC and CC at codon +10 of the TGF-beta1 gene. Our present conclusion is that 509 C>T and +10 T>C TGF-beta1 polymorphisms are associated with Chagas disease susceptibility. Studies in genetically different populations also susceptible to CD will certainly gather new insights on the encouraging use of TGF-beta as a CD biomarker and on the role of immunogenetics in CD pathology.